-4-3D=-10-4d

Simple and best practice solution for -4-3D=-10-4d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-3D=-10-4d equation:



-4-3=-10-4D
We move all terms to the left:
-4-3-(-10-4D)=0
We add all the numbers together, and all the variables
-(-4D-10)-4-3=0
We add all the numbers together, and all the variables
-(-4D-10)-7=0
We get rid of parentheses
4D+10-7=0
We add all the numbers together, and all the variables
4D+3=0
We move all terms containing D to the left, all other terms to the right
4D=-3
D=-3/4
D=-3/4

See similar equations:

| −8+g=9 | | 5(-4-6a)=-20-5a | | 10–2x=19x+2–5x | | 4=4(v-16) | | x^2=12(x+9) | | 1.5x+11=5 | | 2(x-5)=6(x+7 | | 4x-2+7x+1=32 | | x/4+5=37 | | x+5.4=9.4 | | -17=15n-62 | | -16(3n+4)=42 | | 3q+18=180 | | 16-3p=2/3p*5 | | -5x-5+3x=7+4x-9 | | x+−15=23 | | 9+40m=9-7m | | -5y+7(y+2)=6 | | 4(3x-2)=6(2x-3) | | 6x-3+5=2x=18-12+8x | | 3c-6=4 | | 250+25x=-50 | | 7w−3(5+w)=10w+3 | | .9m=75+.7m | | 5(2x+4+6=4(3x+1)-6 | | s+4/3=4 | | -4+6x=-x+24 | | -8x+5(x+3)=18 | | 3b=-9.5 | | 2(300x-900)=3 | | 2x-8(x-8)=112 | | 2x-1=5x-3x-8 |

Equations solver categories